Harmonics Distribution in Electrical Power System Containing Static Var Compensator - Mohammed K. Edan (Engineering and Technology Journal, 2009)
This research presents a harmonic analysis of the power system with static VARcompensator. The model is formed by parallel combination of Thyristor ControlReactor (TCR) with a bank of capacitor .This model based on use of harmonicswitching functions and this harmonic model is completely general and can beinterpreted as a harmonic admittance equivalent. It is suitable for directincorporation into the harmonic domain frame of reference where it combineseasily with frequency dependent admittances of the transmission network, andwith other linearised component. This approach leads to efficient iterative solutionof power networks containing TCR. The general operating condition correspondsto a case, when the switching instant of thyristor valve are function of networknodal voltage conditions, this applies to both thyristor turn-on and turn-offinstants. In such situation the voltage zero crossing points calculated with goodaccuracy at each iterative step, are used to update the TCR switching function.Newton-Raphson technique is used to determine the zero-crossing points.